2015
DOI: 10.1016/j.celrep.2015.10.039
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor Cdkn3 Is Required for Maintaining the Proper Number of Centrosomes by Regulating the Centrosomal Stability of Mps1

Abstract: Supernumerary centrosomes promote the assembly of abnormal spindles in many human cancers. The observation that modest changes in the centrosomal levels of Mps1 kinase can cause centrosome overduplication in human cells suggests the existence of a regulatory system that may tightly control its centrosomal stability. Here, we show that Cdkn3, a Cdk-associated phosphatase, prevents Mps1-mediated centrosome overduplication. We identify Cdkn3 as a direct binding partner of Mps1. The interaction between Mps1 and Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…PIPKIγ restrains centriole duplication by interacting with Plk4 and negatively regulating its kinase activity49. Cdkn3 prevents Mps1 kinase-mediated centrosome over-duplication by regulating Mps1 protein stability50. In addition, KLF14 represses centrosome amplification by transcriptionally inhibiting the Plk4 protein level51.…”
Section: Discussionmentioning
confidence: 99%
“…PIPKIγ restrains centriole duplication by interacting with Plk4 and negatively regulating its kinase activity49. Cdkn3 prevents Mps1 kinase-mediated centrosome over-duplication by regulating Mps1 protein stability50. In addition, KLF14 represses centrosome amplification by transcriptionally inhibiting the Plk4 protein level51.…”
Section: Discussionmentioning
confidence: 99%
“…Because Mps1 centrosomal levels are tightly regulated by the proteasome-dependent degradation of Mps1 at centrosomes (18,20,27), we tested whether the reduced centrosomal accumulation of GFP-Mps1…”
Section: Resultsmentioning
confidence: 99%
“…Another study obtained similar results, revealing that increased expression levels of HIST1H2BM were associated with a poor survival in patients with LUAD and may act as a potential biomarker of drug synergy for the future clinical trials (21). Although in the previous study CDK3 has been reported as a tumour suppressor by maintaining the proper number of centrosomes (22), CDKN3 has also been demonstrated to be a potential poor prognostic marker in LUAD through the systematic analysis of datasets in Lung Cancer Explorer (23). Another report further proved that CDKN3 upregulation, which is mainly caused by the increase of mitotic activity, may be associated with poor survival in patients with LUAD, arguing against CDKN3 as a tumour suppressor (24).…”
Section: Discussionmentioning
confidence: 76%